2018
DOI: 10.1002/adma.201803612
|View full text |Cite
|
Sign up to set email alerts
|

E‐field Control of the RKKY Interaction in FeCoB/Ru/FeCoB/PMN‐PT (011) Multiferroic Heterostructures

Abstract: E-field control of antiferromagnetic (AFM) orders is promising for the realization of fast, compact, and energy-efficient AFM applications. However, as the AFM spins are strongly pinned, the E-field control process is mainly based on the exchange bias regulation that usually confines at a low temperature. Here, a new magnetoelectric (ME) coupling mechanism for the modulation of AFM orders at room temperature is explored. Based on the FeCoB/Ru/FeCoB/(011) Pb(Mg Nb )O -PbTiO (PMN-PT) synthetic antiferromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…These experimental results confirm that the magnetic anisotropy is rotated by 90° via the E-field-induced magnetoelastic coupling between the FL and ferroelectric PMN-PT layers, as shown in Figures S13 B and S13C in the supplemental information . Accordingly, the E-field-induced H eff can reversibly rotate magnetization toward 180° with the aid of successively opposite and small H-fields ( Wang et al., 2018a ; Zhao et al., 2016 ). It is mentionable that the physical limit of E-field-induced 180° magnetization reversal lies in how to break the 2-fold symmetry of the degenerate bistable magnetic states of the FL in MTJs/PMN-PT hybrid structures ( Matsukura et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These experimental results confirm that the magnetic anisotropy is rotated by 90° via the E-field-induced magnetoelastic coupling between the FL and ferroelectric PMN-PT layers, as shown in Figures S13 B and S13C in the supplemental information . Accordingly, the E-field-induced H eff can reversibly rotate magnetization toward 180° with the aid of successively opposite and small H-fields ( Wang et al., 2018a ; Zhao et al., 2016 ). It is mentionable that the physical limit of E-field-induced 180° magnetization reversal lies in how to break the 2-fold symmetry of the degenerate bistable magnetic states of the FL in MTJs/PMN-PT hybrid structures ( Matsukura et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exchange bias field H eb is estimated to be approximately 470 Oe. Additionally, the magnetization switching of the RL is not modulated by the E-field, as shown in the shaded light green in Figure 8D because the SAF structure provides a strong RKKY interaction for the RL (Wang et al, 2018a(Wang et al, , 2018b. From the magnetic hysteresis loop along the minor axis (the [01-1] direction of the PMN-PT substrate), the magnetic switching becomes easier after applying an E-field of 6 kV/cm, as shown in Figure S13A in the supplemental information.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used linear strain effect is proportional to the applied voltage, while the nonlinear strain effect is arising from the 71° and 109° ferroelastic switching which can be generated by a small E‐field near the coercive field . We have measured butterfly‐like strain curve of the PMN‐PT (011) substrate and found that the E‐field induced compressive strain (maximum strain ≈−0.5%) is larger than the tensile strain (maximum strain ≈+0.3%) . This means that the strain effect of the [100] direction can be more remarkable than that of the [01‐1] direction.…”
Section: Resultsmentioning
confidence: 99%
“…But, unfortunately, multiferroics are rare in nature, typically present weak magnetoelectric coupling (BiFeO 3 ) 11 , and require extreme thermodynamic conditions for their synthesis (PbVO 3 and BiCoO 3 ) [12][13][14] . In addition, magnetoelectric multiferroics mostly are antiferromagnetic hence potential applications based on external magnetic bias generally are frustrated due to their little influence on antiparallel magnetic spins 15 . Common strategies employed to synthesize bettered multiferroic materials include doping 16,17 , solid solutions 18,19 , and strain engineering 1,20 .…”
Section: Introductionmentioning
confidence: 99%